Pengaruh Return On Assets (ROA), Debt To Equity Ratio (DER) Dan Current Ratio (CR) Terhadap Harga Saham - Suhartono, suhartono; Novita Damayanti; Lukman Hakim6; Vera Agsutina Yanti; Taat Kuspriyono; Rizky Amalia; abdurrachman, Abdurrachman (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2026)
The capital market is a meeting place for parties with excess funds and those requiring additional capital, both for the short and long term. Profits are calculated by considering the sales yield per share. The stock price itself is the value or price of a share traded on the stock market. This study aims to determine the effect of variables such as Return on Assets, Debt to Equity Ratio, and Current Ratio on stock prices listed on the Indonesia Stock Exchange. This study used a quantitative approach with multiple linear regression using SPSS version 27. The sample was taken using a purposive sampling technique, with 11 companies. The results showed that simultaneously, the variables ROA, DER, and CR had a significant positive effect on stock prices, as indicated by the calculated F value of 12.101, which is greater than the F table of 2.839, with a significance level of 0.001, which is below the 0.05 limit. Partially, only the CR variable had a significant positive effect on stock prices, with a calculated t value of 5.389 and a significance level of 0.001. Meanwhile, the ROA and DER variables did not show a significant effect, with significance levels of 0.383 and 0.393, respectively, exceeding the 0.05 threshold. Keywords: ROA, DER, CR, Stock Price